Water for irrigation at the Antônio Conselheiro settlement, Mato Grosso, Brazil (Research, Society and Development, 2022)
Irrigation is an essential technology for the increase in productivity, improvement of quality of produce, increase in producers’ income, and the good quality of water is fundamental for the success of those benefits. The presence of salts in high concentrations may cause salinization of the soil, toxicity in plants and damage to irrigation equipment, such as sprinkler clogging, which causes environmental and economic losses. This study aimed at characterizing and classifying the quality of water for irrigation in the Antônio Conselheiro Settlement (AAC, in Portuguese) area, located in the state of Mato Grosso, Brazil. Samples were monthly collected from the main water sources in the area, the Sepotuba and Juba rivers, and Tarumã creek, from October 2014 to September 2015. The assessed variables were bicarbonate, calcium, chlorides, electric conductivity, magnesium, pH, and sodium. The results were compared with the parameters established in the literature and were used to classify the waters by means of the Piper diagram and the United States Salinity Laboratory (USSL) diagram. Out of the assessed variables, only electric conductivity, pH and SAR presented restrictions to use in irrigation. The Piper diagram classification indicates the presence of chloride sodic waters (59%), bicarbonate sodic waters (38%), and mixed chloride waters (3%). Good or excellent waters were found in 88.2%. Therefore, the water available in the AAC area, in surface and underground sources, may be used in sprinkler and localized irrigation systems without major harm to the soil or to the crops.